Efeitos imediatos da técnica de vibração sonorizada de língua associada à estimulação nervosa elétrica transcutânea (TENS) - Fabron, Eliana Maria Gradim; Petrini, Andressa Schweitzer; Cardoso, Vanessa de Moraes; Batista, João Carlos Torgal; Motonaga, Suely Mayumi; Marino, Viviane Cristina de Castro (FapUNIFESP (SciELO), 2017)
Purpose: To investigate vocal quality variability after applying tongue trills associated with transcutaneous electrical nerve stimulation (TENS) on the larynx of women with normal laryngeal function. Additionally, to verify the effect of this technique over time on voice quality. Methods: Participants were 40 women (average 23.4 years) without vocal complaints. The procedure involved tongue trills with or without TENS for 3 minutes, rest and repeating the technique for another 2 minutes. The participants' voices were recorded before (Pre), after three minutes (Post 3min) and after two additional minutes (Post 5min) applying the technique. TENS with two electrodes was used on the thyroid cartilage. Self-assessment, acoustic and perceptual analysis were performed. Results: When comparing tongue trills in isolation and associated with TENS, a greater sense of stability in phonation (self-assessment) and improvement in voice quality (perceptual evaluation) was observed in the combination technique. There was no statistical difference in acoustics findings between tongue trills in isolation and associated with TENS. When comparing the time effect of tongue trills with TENS in self-assessment there was a perception of less muscle tension (3min) and greater comfort during phonation (5 min); in the acoustic analysis, there was an increase of F0 (3 and 5 min) and intensity (5 min) when compared to Pre-moment; in the perceptual evaluation, better voice quality (3min). Conclusion: Comparing tongue trills in isolation and associated with TENS, there were changes in the comfort and muscle tension perception, as well as in vocal quality. On the other hand, tongue trills associated with TENS performed in 3 or 5 minutes resulted in beneficial effects on the voice identified in the assessments.
Immediate effects of tongue trills associated with transcutaneous electrical nerve stimulation (TENS)